Diversity in the stellar velocity dispersion profiles of a large sample of brightest cluster galaxies z ≤ 0.3. Issue 1 (23rd February 2018) - Loubser, S I; Hoekstra, H; Babul, A; O'Sullivan, E
Abstract: We analyse spatially resolved deep optical spectroscopy of brightestcluster galaxies (BCGs) located in 32 massive clusters with redshifts of 0.05 ≤ z ≤ 0.30 to investigate their velocity dispersion profiles. We compare these measurements to those of other massive early-type galaxies, as well as central group galaxies, where relevant. This unique, large sample extends to the most extreme of massive galaxies, spanning M K between –25.7 and –27.8 mag, and host cluster halo mass M 500 up to 1.7 × 10 15  M⊙ . To compare the kinematic properties between brightest group and cluster members, we analyse similar spatially resolved long-slit spectroscopy for 23 nearby brightest group galaxies (BGGs) from the Complete Local-Volume Groups Sample. We find a surprisingly large variety in velocity dispersion slopes for BCGs, with a significantly larger fraction of positive slopes, unique compared to other (non-central) early-type galaxies as well as the majority of the brightest members of the groups. We find that the velocity dispersion slopes of the BCGs and BGGs correlate with the luminosity of the galaxies, and we quantify this correlation. It is not clear whether the full diversity in velocity dispersion slopes that we see is reproduced in simulations.